Precision and accuracy of stereotactic convergent beam irradiations from a linear accelerator - Hartmann, Günther H.; Bauer-Kirpes, Bernhard; Serago, Christopher F.; Lorenz, Walter Josef (International journal of radiation oncology, biology, physics, 1994)
Purpose: The accuracy and the precision for radiosurgery procedures at linear accelerator facilities were investigated. Methods and Materials: The technique of convergent beam irradiation, that is a series of successive isocentric arc irradiations, is specifically considered in this paper. Accuracy and precision depend on a sequence of methods and equipment among which localization of the target, patient alignment, and the dose delivery are the most critical steps. The purpose of the investigation was to quantitatively assess their contribution to the overall accuracy. The definitions and methods used to quantify and control accuracy are described. Measurements were carried out at a phantom to analyze the localization and positioning errors. Errors which may occur with the dose delivery technique were studied by it computer simulation. Results: The calculations showed that these errors are not the main contributors to the overall accuracy as long as the linac inaccuracies are in the order or less than 1 mm. The accuracy found in the localization and positioning methods was less than 1 mm. Conclusion: It was concluded that an overall accuracy in the order of 1 mm can be obtained also under routine conditions. The great importance of adequate quality control is emphasized.
Elektronische Reproduktion der Druck-Ausgabe 22. Dezember 2009
Gesehen am 30.07.2025